The youngest preschool children: Community in play - Pálmadóttir, Hrönn; Einarsdóttir, Jóhanna (Icelandic Journal of Education, 2015)
The aim of this study is to shed light on young children’s perspectives on their social interactions in play situations in preschool. Participants in the study were a group of twenty children, with ages ranging from fourteen months to two years and five months old. The children attended preschool in Iceland. Four adults, including two preschool teachers who worked with the children, also participated. The study is based on the phenomenological approaches emphasizing human bodily existence put forth by French philosopher Maurice Merleau-Ponty (1962, 1994), whose concept of the life world describes the intertwined relations between human beings and the environment. The body is the foundation for the existence of the child. The child is viewed as an active body that is already engaged with its physical and social environment and in the process of making sense out of the experience (Johansson, 1999; Merleau-Ponty, 1962, 1994). The life world is the meaningful context that helps people understand and interpret their environment. Children’s play has roots in movement of the body (Åm, 1989; Hangaard Rasmussen, 2001), and intersubjectivity between partners is an important part of the process that occurs when children mutually create their communities in play situations. The study was conducted over a five month period, and qualitative methods were employed, including participant observations, video recordings, and field notes. The focus was on children’s communication when they started play, how they continued the play, and how they tried to gain access to play that had already started. In approaching and interpreting children’s perspectives it is necessary to gain access to children’s actions in their own life worlds. The resulting portrait of children’s perspectives is connected to the ontological stance of the researcher and how he understands, interprets, and presents the data gathered. The objective of this study is to understand children’s actions, their intentions and views, as well as to interpret their ...